Biomass oxy-fuel combustion technology as carbon neutral renewable source of energy to replace fossil fuels - Sher, Farooq (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2022)
Due to growing concerns about climate change, the heat and power sector is continuously facing challenges to reduce CO2 emissions. Carbon capture and storage (CCS) is one of the short-medium term measures that can mitigate CO2 emissions emitted from fossil fuels utilisation. Oxy-fuel combustion is a promising technology for CSS that can be integrated into the new and the current fleet of power plants. Biomass is a carbon-neutral renewable source of energy that can replace fossil fuels. If the biomass is utilised as a fuel in oxy-fuel combustion it could lead even to negative CO2 emissions. However, oxy-fuel combustion technology in fluidised beds is in the early stages of development and still needs a lot of research for improvement before its application on full-scale power plants. The basic combustion fundamentals of different biomass fuels in terms of energy production were studied using thermogravimetric analysis (TGA) under air, N2, CO2 and selected oxy-fuel (30%O2/70%CO2) reaction environments. Then a 20 kWth bubbling fluidised bed combustor (BFBC) was designed, manufactured and successfully tested for a range of biomass fuels under air and oxy-fuel combustion environments. The agglomeration and sintering behaviour of these biomass fuels during combustion under air was also investigated using different analytical techniques such as SEM-EDX, XRD and XRF. The biomass fuels investigated include domestic wood, industrial wood, miscanthus, wheat straw and peanut shell pellets. The BFBC testing of these biomass fuels focused on the influence of operating conditions, the effect of excess air level and fuel feed rate on the hydrodynamics, temperature profiles and emissions, NOx, CO2 and CO within the BFBC.